Oral versus intravenous Paracetamol and Ketorolac in postoperative pain management following laparoscopic cholecystectomy: A prospective comparative study - Rokaya, Ashok Kumar; Badal, Anil Singh; Gyawali, Sagar; Shahi, Dinesh; Acharya, Kalpana; Chaudhary, Gyanesh; Maharjan, Shanta Bir; Paudyal, Sanjay (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Pain following laparoscopic cholecystectomy is multifactorial and necessitates a multimodal approach for management. Paracetamol and Ketorolac are commonly used as part of a multimodal analgesic regimen postoperatively. This study aimed to compare the efficacy of oral paracetamol and ketorolac with intravenous paracetamol and ketorolac for pain management after laparoscopic cholecystectomy. Methods: A prospective cross-sectional comparative study was conducted on 106 patients who underwent laparoscopic cholecystectomy between August 2022 and July 2023. The patients were divided into two equal groups of 54 each: the OPK group (oral paracetamol and ketorolac) and the IPK group (intravenous paracetamol and ketorolac). The primary outcome was a visual analog scale (VAS) score measured 8 h after the operation and on the first postoperative day at 0800h. The secondary outcome was the amount of tramadol used for rescue analgesia. Results: Most participants were female (67.6%), and the mean age of the population was 44.83±1.27 years. The mean VAS scores measured at 8 hours postoperatively and on the first postoperative day in the OPK and IPK groups were not statistically different (5.85±1.52 vs. 6.24±1.32; p=0.28, and 3.21±1.30 vs. 3.50±1.46; p=0.24, respectively). The mean tramadol required as rescue analgesia was higher in the intravenous group (74.07±39.74 mg) than in the oral group (66.67±38.85 mg); however, the difference was not statistically significant (p=0.33). Conclusion: Our study demonstrated comparable efficacy of oral and IV routes of paracetamol and ketorolac for postoperative pain management following laparoscopic cholecystectomy